PENGARUH KINERJA ESG TERHADAP BIAYA UTANG DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Non-Keuangan Yang Terdaftar di BEI Tahun 2018-2024) - Na’imah Na’imah; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of ESG performance on debt costs, with audit quality serving as a moderating variable. The independent variable used is ESG performance, while the dependent variable is debt costs. Audit quality, as the moderating variable, is proxied by audit costs and the use of a BIG4 accounting firm. The sample for this study consists of non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2024, totaling 14 companies. Purposive sampling was used as the sampling method. The study employs panel data regression analysis to test the effect of ESG performance on debt costs and uses Moderated Regression Analysis to test the moderating variable.The results indicate that ESG performance has a significant positive effect on debt costs. This positive relationship suggests that companies that increase their ESG performance disclosures will actually incur higher debt costs. However, the study found that audit costs do not affect the relationship between ESG performance and debt costs; nevertheless, companies audited by BIG4 firms tend to have lower debt costs regardless of their ESG level.